Nursing care in early childhood: contributions from intersubjective recognition - Débora Falleiros de Mello; Monika Wernet; Maria de La Ó Ramallo Veríssimo; Vera Lúcia Pamplona Tonete (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to understand the elements composing intersubjective recognition that are relevant for nursing care in early childhood in favor of comprehensive child development. Method: reflexive study based on the Honnethian concept of intersubjective recognition in the dimensions of affection, defense of rights, and social esteem. Results: nursing knowledge and practices, permeated by the intersubjective recognition in the mentioned dimensions, contribute to the dynamism of interpersonal relations, the production of co-responsibility, and shared construction of health care in early childhood, with benefits to comprehensive development. Conclusion: a successful coordination of the three intersubjective dimensions enables the expansion of the understanding on childhood and nursing care in child health in the field of human development promotion, covering affection, defense of rights, and social esteem in the established relationships with future positive individual and social possibilities.